The Representation of Indonesian Females Working as Domestic Migrant Workers: A Comparative Analysis on Arab News Online and Jakarta Post Online - Hendar,; Zuraida, Ida; L. Sujatna, Meita; Farida, Sasmi (International Journal of Psychosocial Rehabilitation, 2020)
The research dealing with both printed and electronic mass media is interesting because they not only become more and more progressive in terms of technology, starting from manual to digital uses of technology, but also various themes can be analyzed from rhetoric, semiotics, framing, and critical points of view, such as critical discourse analysis. The objective of this descriptive qualitative research is to analyze the representation of Indonesian female domestic migrant workers in news language texts in both English media, Arab News Online, and The Jakarta Post Online, taken place before and after moratorium periods. The main data of this research is, therefore, the language used in news texts regarding Indonesian female domestic migrant workers in Saudi Arabia before and after moratorium periods. To obtain the objective of the research above, Van Dijk’s model of critical discourse analysis is used to analyze and describe a news text as social reality, focusing on the microstructure, superstructure, and macrostructure of the texts. The result of this research shows that the Indonesian females working as domestic migrant workers in Arab Saudi Arabia are represented negatively and unappreciatively; conversely, the Jakarta Post represents them positively and appreciatively.